Stability Control of Multilayer Roof Strata in the Large Mining Height Gob-Side Entry: A Case Study - Yong Chen; Yingpeng Wang; Zhengyuan Qin; Feng Yang; Vivek Agarwal (Applied Sciences)
Roof separation, destabilization and collapse of multilayer roof structures are difficult to control in large mining height gob-side entries due to severe mining pressure. In the 22301 working face in Tunlan Mine, a mining height of 4.75 m posed great challenges to gob-side entry retaining techniques. Through mechanical analysis, the strata movement of a multilayer roof structure was investigated, and numerical analysis was conducted to identify key aspects of the supporting scheme, e.g., ensuring the stability of immediate roof above the filling area, transferring the resistance from the cemented backfill to the roof structure and maintaining self-supporting capacity. A new support strategy was proposed and applied in industrial settings, with entry stability evaluated by monitoring the deformation characteristics, roof separation values and overall support performance. The results showed that the gob-side entry retaining technique was successful in Tunlan Mine, providing valuable insights for similar techniques in large mining height gob-side entries.